High pT π0 production from αα and αp collisions at the CERN ISR - Angelis, A; Basini, G; Besch, H; Breedon, R; Camilleri, L; Chapin, T; Cool, R; Cox, P; von Gagern, C; Grosso-Pilcher, C; Hanna, D; Linnemann, J; et al. (1982)
The invariant cross sections for π0 meson production in alpha-alpha and alpha-proton collisions at the ISR were meas- ured up to transverse momenta of 7 GeV c and 8 GeV c, respectively. These measurements are compared with π0 production in pp collisions at the same values of s/nucleon, and the variation of the nuclear A-dependence with pT is determined. © 1982.